(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Impaired male reproductive function is a major complication associated with diabetes mellitus (DM). Whether or not insulin, when co-administered with zinc will reverse or ameliorate reproductive dysfunction in male diabetics is not known. This study thus sought to establish if co-administration of insulin and zinc reverses or ameliorates male reproductive dysfunction in DM better than either insulin or zinc. Five (5) normal and twenty (20) diabetic sexually mature rats were assigned into five groups of five animals each. Group A consisted of normal rats and had access to only food and water. Group B consisted of diabetic animals with no treatment and served as DM control. Groups C and D consisted of diabetic animals and received insulin and zinc respectively. Group E consisted of diabetic animals and received both insulin and zinc. All diabetic animals had free access to food and water. Insulin in all cases was given subcutaneously twice daily in the morning and evening at 1 unit and 4 units respectively. Zinc (10mg/kg) was given orally once daily. Treatments in all cases commenced two weeks after DM was confirmed. The treatment lasted ten days. Samples were thereafter collected for analyses. DM decreased sperm count, sperm motility, sperm viability, normal sperm cells, semen pH, serum follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone, while increasing sperm cells with defective tails. DM also impaired testicular morphology. Insulin and zinc co-administration improved sperm viability, sertoli cell count, Johnsen’s score, serum FSH, LH and testosterone. Co-administration also improved semen pH towards normal. Insulin or zinc ameliorated several aspects of DM-induced male sexual dysfunction. However, the co-administration of insulin and zinc provided better results.